PRACTICES OF COLLATERAL GOODS AUCTION AT BANJARMASIN SHARIA PAWNSHOPS (BANJARMASIN ULAMA PERSPECTIVE ANALYSIS) - Umi Hani; Parman Komarudin; Rahmatul Huda; Abdul Hadi; Zakiyah Zakiyah (Badamai Law Journal, 2023)
Auction is the sale of goods in public which is preceded by efforts to gather interested parties through announcements made by and in front of the auction official with the achievement of the optimal price through verbal bidding up and down or down and or in writing. The process of the role of the ulema in society, makes the ulema not only have theological validity but also social validity and its existence is firmly rooted in society. From this it can be understood that scholars are not only followed by their opinions in the religious field, but even in the social field, including the economic field. Many say that Banjarmasin is a religious city, it can be seen that the people of Banjarmasin are still strong in following the opinions/words of the scholars. The formulation of the problem in this paper is how is the practice of auctioning collateral at sharia pawnshops in Banjarmasin and how is the perspective of Ulama Banjarmasin the practice of auctioning collateral. This study uses qualitative research with the type of field research (field research), the nature of the research is a case study (case study). The results of this study are that there are two methods used in the auction system, namely open auctions and closed auctions. A closed auction is an auction in which the applicant submits the price of the property he is interested in in a sealed or confidential envelope. Meanwhile, in the opinion of the Banjarmasin scholars, the practice of auctioning collateral items is not prohibited by sharia and the law is permissible as long as it is in accordance with the provisions of the DSN-MUI Fatwa, Guarantees in sharia pawnshops function as proof of the customer's commitment to paying off the financing.